Program Cantas Gagal for CEW541 & CEW547: Engineering Hydrology workshop - Ahmad Mohtar, Intan Shafeenar; Muhamad Bashar, Nur Azwa; Kuan, Woei Keong (Unit Penerbitan FKAPP, 2025)
Approximately 100 students from the CEW541 and CEW547 Engineering Hydrology courses participated in a focused and impactful learning session under the Program CANTAS GAGAL — a special hands-on workshop designed to strengthen students’ understanding and performance in Engineering Hydrology. This initiative was guided by three passionate facilitators-Dr. Intan Shafeenar Ahmad Mohtar, Ir. Nur Azwa Binti Muhamad Bashar and Dr. Kuan Woei Keong. The main aim of this workshop was to ensure that all students can pass the course by providing additional support, clarification, and practical exposure to the subject matter. The program was carefully structured to help students overcome common misconceptions, build confidence, and master key topics in Engineering Hydrology through a combination of thorough discussions and interactive hands-on sessions. Each topic was covered in detail by the facilitators, with clear explanations and real-life examples. The workshop’s title, “CANTAS GAGAL”, captured its mission — to eliminate failure by addressing learning gaps and reinforcing core concepts. The facilitators also highlighted important professional values such as teamwork, data accuracy, and responsibility in engineering work.